2016
DOI: 10.1186/s40809-016-0013-6
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of a targeted posterior fossa multimodal stroke protocol for the diagnosis of acute posterior ischemic stroke

Abstract: Background: There is limited but growing research regarding the accuracy of CTP in diagnosing acute posterior ischemia stroke. We sought to evaluate the diagnostic accuracy of an incremental multimodal CT protocol in acute posterior ischemic stroke. Methods: Retrospective review of incremental NCCT, CTA-source images and CTP use in 82 consecutive patients with acute posterior ischemic stroke. Readers were blinded to infarct status on follow-up imaging (MRI or CT). Predictive effects of observed diagnostic accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
(44 reference statements)
1
10
0
Order By: Relevance
“…Few other studies have tested the performance of CTP in this stroke territory [6][7][8][9][10]14]. A subgroup analysis from the Dutch Acute Stroke Trial (DUST) showed that the addition of CTP increases the detection rate of early ischaemic changes in the posterior circulation compared to combinatory NCCT and CTA [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few other studies have tested the performance of CTP in this stroke territory [6][7][8][9][10]14]. A subgroup analysis from the Dutch Acute Stroke Trial (DUST) showed that the addition of CTP increases the detection rate of early ischaemic changes in the posterior circulation compared to combinatory NCCT and CTA [7].…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography with CT perfusion (CTP) approximately doubles the detection rate of acute ischaemia compared to plain CT . Whilst there has been extensive research concerning the diagnostic and prognostic value of CTP in the anterior circulation, there is only little evidence regarding the posterior circulation . The clinical and imaging parameters associated with focal hypoperfusion on acute CTP were explored in patients with posterior circulation stroke and it was hypothesized that CTP hypoperfusion is an independent predictor of clinical outcome in such patients.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic value of CTP in the posterior circulation has been little investigated with few evidences of its reliability and accuracy; moreover, the diagnostic effects of RAPID introduction in the evaluation of infratentorial ischaemic changes have not yet been clarified [ 3 , 4 , 38 40 ]. To the best of our knowledge, these are the first reported instances of PC stroke patient selection using RAPID from European countries.…”
Section: Introductionmentioning
confidence: 99%
“…To date, Computed Tomography (CT) is the most applicable tool for rapid screening of ischemic in medical emergency [3] [6] [7]. Despite that, the diagnosis of ischemic in CT slices of Posterior Fossa (PF) remains as the most challenging area, which demands the expertise of radiologist [8]- [10]. The diagnosis process can be monotonous and time-consuming.…”
Section: Introductionmentioning
confidence: 99%